Educational Fiqh: The Viewpoints of Sheikh Arsyad Al Banjari and Az Zuhaili on the Method for Determining Marriage Witnesses - ., Rusdiyah; Seff, Nadiyah; Zaidah, Yusna; ., Sa'adah; Sulistyoko, Arie; Hafidzi, Anwar; ., Faridah (KnE Social Sciences, 2023)
This research examined the means of determining marriage witnesses in the Marriage Books from Sheikh Arsyad al-Banjari and Wahbah Az-Zuhaili. Marriage witnesses are a pillar of marriage that should not be neglected. Thus, one must adhere to some prerequisites to qualify as a marriage witness. This study employed a literature evaluation with the primary sources of Sheikh Arsyad al-Banjari’s Kitabun Nikah and the Islamic Book of Fiqh Islam Wa Adillatuhu and supporting data from numerous Banjar of South Kalimantan’s perspectives. The findings were examined descriptively and qualitatively. The results of this study demonstrated that according to Sheikh Arsyad Al-Banjari in the Kitabun Nikah, the provisions of the marriage witness are not to be mute, not to fight, and not to be the child of the bride and groom. In contrast, Wahbah az-Zuhaili in the Book of Fiqh Islam Wa Adillatuhu permits it, as children and enemies can witness the marriage. Keywords: Determining, Marriage, Method, Witnesses